Association of carotid artery stenosis with cerebral artery signal intensity gradient on time-of-flight magnetic resonance angiography - Lee, Chan-Hyuk; Jeong, Seul-Ki; Kim, Hyun Jin; Rosenson, Robert S.; Yang, Wookjin; Jung, Keun-Hwa (Frontiers in Neurology, 2025)
PurposeExtracranial internal carotid artery (ICA) stenosis is a known cause of large artery ischemic stroke. However, its association with cerebral arterial hemodynamics has been relatively underexplored. This study investigates the relationship between extracranial ICA stenosis and signal intensity gradient (SIG) in major cerebral arteries. The SIG is a surrogate marker for arterial wall shear rate.MethodsIn the cross-sectional, retrospective study, we included individuals who underwent health screenings for vascular risk factors, as well as Time-of-Flight Magnetic Resonance Angiography and carotid Doppler ultrasonography. Extracranial ICA stenosis was categorized into three groups: normal, <50% stenosis, and ≥50% stenosis. In each group, SIGs were measured in major cerebral arteries. The association between ICA status and SIG in major cerebral arteries was analyzed using logistic regression, with SIG tertiles as the variable of interest.ResultsA total of 1,138 individuals (mean age ± SD, 63.3 ± 9.6 years) were included. ICA stenosis ≥50% was significantly associated with cerebral artery SIGs, with age and basilar artery (BA) SIG showing the strongest correlations. Multinomial logistic regression revealed that individuals in the lowest tertile of BA SIG had a significantly higher odds ratio (OR) for ICA stenosis (OR: 2.72, 95% CI: 1.27–5.82; p = 0.010) compared to those in the highest tertile.ConclusionICA stenosis is significantly correlated with BA SIG, indicating a possibility of link between ICA stenosis and intracranial hemodynamics. A prospective longitudinal study is warranted to clarify the causal link between ICA stenosis and BA SIG.